C8-modified CeO2//SiO2 Janus fibers for selective capture and individual MS detection of low-abundance peptides and phosphopeptides. Issue 25 (9th June 2016) - Lv, Nan; Wang, Zhigang; Bi, Wenzhi; Li, Guangming; Zhang, Jilin; Ni, Jiazuan
Abstract : The novel CeO2 //SiO2 -C8 probe with a Janus structure can selectively extract low-abundance peptides and phosphopeptides from biosamples for individual MS detection. Abstract : The novel chloro(dimethyl)octylsilane (C8)-functionalized [CeO2 //SiO2 ] Janus fibers (denoted CeO2 //SiO2 -C8) have been successfully prepared by electrospinning technique and subsequent modification. The CeO2 //SiO2 -C8 Janus fiber composed of the side-by-side CeO2 fiber and SiO2 fiber modified by C8 is endowed with separate affinity sites and hydrophobic chains. It has a relatively high specific surface area of 127.4 m 2 g −1 with an average pore size of 4.1 nm. The potential of CeO2 //SiO2 -C8 Janus fibers for the selective capture and individual MS detection of low-abundance endogenous peptides and phosphopeptides from the tryptic protein digest and human serum real sample was explored and evaluated for the first time. The experimental results demonstrate that the CeO2 //SiO2 -C8 Janus fiber can selectively extract phosphopeptides in virtue of high selective affinity of CeO2 to phosphate groups and enrich low-abundance peptides on account of the strong hydrophobic interaction of C8 chains. Moreover, the enrichment performance of the CeO2 //SiO2 -C8 probe is superior to that of commercial products ( e.g. TiO2 nanoparticles and ZipTipC18 pipette tips) available. Overall, the efficient enrichment capability of CeO2 //SiO2 -C8 Janus fibers makes them a prospective candidate for the capture of low-abundance endogenous peptides and phosphopeptides from complex biological samples for individual MS detection.